Нормативне забезпечення облікового відображення кредиторської заборгованості - Приходько, Ігор Павлович; Prykhodko, Ihor; Бардадим, Марія Василівна; Bardadym, Mariya; Горбенко, К. А.; Gorbenko, K. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
Сучасні умови господарювання вимагають об'єктивної оцінки довіри до партнерів, а також фінансовоїстійкості та платоспроможності. Економічна стабільність неможлива без фінансової стійкості підприємств, однак саме вона забезпечує їх стійке положення на та конкурентоспроможність ринку. Кредиторська заборгованість дозволяє тимчасово використовувати позикові кошти, проте водночас це зниження платоспроможності та ліквідності. Крім того, наявність прострочених зобов'язань може негативно вплинути на репутацію підприємства. Слід зазначити, що завдяки ефективному управлінню кредиторською заборгованістю, можна мінімізувати її негативні наслідки.Визначено, що досліджуючи положення, що складаються в МСБО 37 та НП(С)БО 11, можна відзначити численні відмінності, що сто суються термінології, класифікації зобов'язань, їх оцінки та відображення інформації про зобов'язання у фінансовій звітності. Отже, можна стверджувати, що питання уніфікації НП(С)БО 11 з МСБО 37 потребує значних доопрацювань і доповнень для адаптації до конкретних українських умов ведення господарської діяльності, з надання покращення системи бухгалтерського обліку в Україні. Borrowed funds are one of the sources of financial resources for enterprises. However, recently, there has been a growing trend when borrowed funds are used not for development and production efficiency, but mainly to repay debts to other creditors. Erroneous accounting, valuation and repayment of current payables can disrupt financial and settlement discipline. The current business environment requires an objective assessment of trust in partners, as well as financial stability and solvency. Accounts payable allow you to temporarily use borrowed funds, but at the same time it reduces solvency and liquidity. Accounts payable represent the company's liabilities to other legal entities or individuals arising from previous transactions and denominated in UAH, which are due on a specified date. It accounts for a significant level of the company’s current liabilities, so it is important to ensure the reliability of this indicator for complete and objective financial reporting. It is stated that in Ukraine, accounting for accounts payable as part of the liability balance sheet is regulated by the Law of Ukraine "On Accounting and Financial Reporting in Ukraine". The methodological principles for the formation and recognition of liabilities in accounting and financial statements are set out in the National Accounting Regulation (Standard) 11 "Liabilities". At the same time, after the national standards are created on the basis of international standards, they should not add the latter, which necessitates the use of International Accounting Standards(IAS). In international practice, accounting for liabilities is regulated by IAS 1 Presentation of Financial Statements, AS 32 Financial Instruments: Disclosure and Presentation, and IAS 37 Provisions, Contingent Liabilities and Contingent Assets. It is recognized that the classification and measurement of liabilities (payables) in accordance with International Financial Reporting Standards are key aspects that require detailed consideration. An enterprise's liabilities to external parties are governed by numerous international standards characterized by complex terminology
Regulatory provision of accounting display creditor indebtedness
Keywords: нормативне забезпечення; regulatory support; облікове відображення; accounting; кредиторська заборгованість; accounts payable; зобов'язання; liabilities